2021
DOI: 10.1016/j.eclinm.2021.101060
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional analysis of racial differences in accelerated aging and cognitive function among patients with atrial fibrillation: The SAGE-AF study

Abstract: Background Non-Whites are more likely to suffer from cognitive impairment and complications of atrial fibrillation (AF) than Whites, though Whites are more likely to be diagnosed with AF. We examined whether non-Whites with AF are biologically older than Whites with AF and whether accelerated biological aging is associated with cognitive functioning. Methods We used baseline data from the ongoing Systematic Assessment of Geriatric Elements in Atrial Fibrillation prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Accelerated aging was associated with various categories of diseases. Recent studies have shown that aging acceleration was associated with cardiovascular diseases, depression and anxiety, diabetes, and cognitive impairment (Chen et al, 2023 ; Forrester et al, 2021 ; Gao et al, 2023 ; Gialluisi et al, 2022 ). Our study identified some novel associations of biological age gap, thus expanding the clinical significance of biological aging.…”
Section: Discussionmentioning
confidence: 99%
“…Accelerated aging was associated with various categories of diseases. Recent studies have shown that aging acceleration was associated with cardiovascular diseases, depression and anxiety, diabetes, and cognitive impairment (Chen et al, 2023 ; Forrester et al, 2021 ; Gao et al, 2023 ; Gialluisi et al, 2022 ). Our study identified some novel associations of biological age gap, thus expanding the clinical significance of biological aging.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, non-Hispanic Whites may be more susceptible to periodontal intervention for preventing aging-related mortality. Since non-Hispanic Whites have less accelerated aging than other races (Forrester et al 2021), they are prone to reverse or slow the aging process by modifiable risk factors. However, future large-scale randomized controlled trials are needed to confirm the beneficial effect of periodontal health care and treatment of periodontitis on delaying the aging process and reducing death rates in the middle-aged and older population.…”
Section: Discussionmentioning
confidence: 99%